2006
DOI: 10.1088/0305-4470/39/21/s79
|View full text |Cite
|
Sign up to set email alerts
|

The Casimir free energy in high- and low-temperature limits

Abstract: The problem with the temperature dependence of the Casimir force is investigated. We analyse high-temperature limit analytically making calculations at real frequencies. The purpose is to answer the question why there is no continuous transition between real and ideal metals and why the result does not depend on the relaxation frequency. It is found that the contribution of evanescent s polarized fields is finite even for an infinitely small relaxation frequency (plasma model) and exactly cancels the contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
(49 reference statements)
4
29
0
Order By: Relevance
“…For pure metals, where the anomalous skin effect theory must be used, the situation is quite interesting. As it was shown by Svetovoy and Esquivel [8], in this case |∂S C /∂l| ∝ T , while |S C | ∝ T 2/3 (see next section). Thus |S C | ≫ |∂S C /∂l|.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…For pure metals, where the anomalous skin effect theory must be used, the situation is quite interesting. As it was shown by Svetovoy and Esquivel [8], in this case |∂S C /∂l| ∝ T , while |S C | ∝ T 2/3 (see next section). Thus |S C | ≫ |∂S C /∂l|.…”
supporting
confidence: 70%
“…Recently much attention has been devoted to the calculation of the entropy related to the Casimir-Lifshitz forces [1][2][3][4][5][6][7][8]. The common point of these papers is the calculation of the so-called "Casimir entropy", which is defined as…”
Section: Physical Meaning and Properties Of The "Casimir Entropy"mentioning
confidence: 99%
“…It is not clear for the moment how realistic is this suggestion but in this paper it is shown that the repulsion can dominate at least for the thermal part of the force.The thermal force also revealed interesting cancelations between EW and PW contributions. At large distances significant cancelations are realized for dielectrics [12] and metals [14]. The cancelation is reduced in the non-equilibrium situation when the temperatures of the bodies are different [12].…”
mentioning
confidence: 99%
“…For the class I materials the calculations were performed in [12] but the distance dependent leading term was presented in [24]: F % À0:0193T 2 a! 2 p @v F c 2 ;…”
mentioning
confidence: 99%